Notch Signaling Mediates Secondary Senescence - Teo, Yee Voan; Rattanavirotkul, Nattaphong; Olova, Nelly; Salzano, Angela; Quintanilla, Andrea; Tarrats, Nuria; Kiourtis, Christos; Müller, Miryam; Green, Anthony R.; Adams, Peter D.; Acosta, Juan-Carlos; Bird, Thomas G.; et al. (Cell reports (Cambridge), 2019)
Oncogene-induced senescence (OIS) is a tumor suppressive response to oncogene activation that can be transmitted to neighboring cells through secreted factors of the senescence-associated secretory phenotype (SASP). Currently, primary and secondary senescent cells are not considered functionally distinct endpoints. Using single-cell analysis, we observed two distinct transcriptional endpoints, a primary endpoint marked by Ras and a secondary endpoint marked by Notch activation. We find that secondary oncogene-induced senescence in vitro and in vivo requires Notch, rather than SASP alone, as previously thought. Moreover, Notch signaling weakens, but does not abolish, SASP in secondary senescence. Global transcriptomic differences, a blunted SASP response, and the induction of fibrillar collagens in secondary senescence point toward a functional diversification between secondary and primary senescence. [Display omitted] •Primary senescence and secondary senescence are distinct molecular endpoints•Secondary Ras-induced senescence has a composite SASP, Notch-induced signature•Notch signaling is an essential driver of secondary senescence•Notch blunts the senescence-associated secretory phenotype in secondary senescence Teo et al. found that secondary senescence in vitro and in vivo requires Notch, rather than SASP alone, as previously thought. The authors show that primary and secondary senescence are distinct molecular endpoints. A blunted secretory phenotype and the induction of fibrillar collagens in secondary senescence point toward functional diversification.